Addressing Passivation in Lithium–Sulfur Battery Under Lean Electrolyte Condition. (23rd February 2018) - Pan, Huilin; Han, Kee Sung; Engelhard, Mark H.; Cao, Ruiguo; Chen, Junzheng; Zhang, Ji‐Guang; Mueller, Karl T.; Shao, Yuyan; Liu, Jun
Abstract: Reducing the electrolyte amount is critical for the high specific energy of lithium–sulfur (Li–S) batteries in practice. The reduced electrolyte condition (a so‐called "lean electrolyte") raises a complex situation for sulfur redox reactions since the reactions rely on the electrolyte mediation. The insulating nature of discharge product Li2 S and its uncontrollable accumulation (passivation) at the cathode interface is one of the major challenges for stable cycling of a Li–S battery under lean electrolyte condition. In this study, it is presented that the NH4 TFSI additive in electrolyte solution greatly alleviates the passivation issue in Li–S batteries under lean electrolyte conditions. The ammonium additive enhances the dissociation of Li2 S and largely reduces the insoluble and large Li2 S particles in the sulfur cathodes, which facilitate the reversible and sustainable redox reactions of sulfur. Therefore, the cycle life of Li–S batteries under lean electrolyte conditions is significantly improved. In addition, it is found that the morphology of Li anodes is dependent on the cathode structures. An ammonium additive enables homogeneous surface of cathode and Li anode and extended cycle life. Abstract : Addressing the passivation issue of insulating Li2 S is extremely critical to extend the cycle life of lithium–sulfur batteries, especially under the lean electrolyte condition. An electrolyte additive promoting the dissociation of Li2 S is an effective solution to prevent the uncontrollable accumulation of Li2 S, leading to an active S cathode interface and homogeneous Li metal deposition morphology.